Evaluation of microcurrent electrical nerve stimulation (MENS) effectiveness on muscle pain in temporomandibular disorders patients Avaliação da efetividade da estimulação neural elétrica por microcorrente (MENS) na dor muscular em pacientes com desordem temporomandibular - Paulo Renato Junqueira Zuim; Alicio Rosalino Garcia; Karina Helga Leal Turcio; Marcelo Matida Hamata (University of São Paulo, 2006)
The effect of Microcurrent Electrical Nerve Stimulation (MENS) was evaluated and compared with occlusal splint therapy in temporomandibular disorders (TMD) patients with muscle pain. Twenty TMD patients were divided into four groups. One received occlusal splint therapy and MENS (I); other received splints and placebo MENS (II); the third, only MENS (III) and the last group, placebo MENS (IV). Sensitivity derived from muscle palpation was evaluated using a visual analogue scale. Results were submitted to analysis of variance (p<0.05). There was reduction of pain level in all groups: group I (occlusal splint and MENS) had a 47.7% reduction rate; group II (occlusal splint and placebo MENS), 66.7%; group III (MENS), 49.7% and group IV (placebo MENS), 16.5%. In spite of that, there was no statistical difference (analysis of variance / p<0.05) between MENS and occlusal splint therapy regarding muscle pain reduction in TMD patients after four weeks. A efetividade da Estimulação Neural Elétrica por Microcorrente (MENS) foi avaliada e comparada à terapia por Placas Oclusais em pacientes com desordens temporomandibulares (DTM) de origem muscular. Vinte pacientes foram divididos em quatro grupos. Um recebeu a terapia por placas interoclusais e MENS (I); outro, placas e MENS placebo (II), o terceiro, somente MENS (III) e o último grupo, MENS placebo (IV). Os resultados obtidos foram submetidos a uma análise de variância (p<0,05). Houve redução dos níveis de dor em todos os grupos: o grupo I (placas e MENS) obteve uma taxa de redução de 47,7%; o grupo II (placa e MENS placebo), 66,7%; o grupo III (MENS), 49,7% e o grupo IV (MENS placebo), 16,5%. Apesar disso, não se verificaram diferenças estatisticamente significantes entre MENS e utilização de placas interoclusais em relação à diminuição de dor muscular em pacientes com DTMs após 4 semanas.